Issues and challenges regarding the determination of the normative monetary valuation of land plots within the territory of the territorial communities - Dorosh, Y.; Tarnopolskyi, А.; Dorosh, A.; Dorosh, О. (Land Management, Cadastre and Land Monitoring, 2023)
A detailed study and analysis of the methodology for the normative monetary valuation of land plots approved by the Resolution of the Cabinet of Ministers of Ukraine dated November 3, 2021 No. 1147 was carried out regarding the possibility of its application, and the identification of problems arising in the process of its implementation. The main aspects of the normative monetary valuation of land plots and its influence on the development of territorial communities in Ukraine are considered. The methodical, economic and regulatory problems of determining the normative monetary valuation of land plots according to the current methodology as an important economic tool for regulating land relations and economic stimulation of rational use and protection of land have been studied and analysed.Methodological and technical deficiencies were identified in the process of determining the normative monetary valuation of land plots of territorial communities and calculating the size of the normative monetary valuation of a separate land plot.It was established that although according to the Law of Ukraine "On Land Valuation" the normative monetary value is "capitalized rental income", the current method of its determination is not based on the income that can be obtained from the use of the land plot, but on fixed tabular norms, which are differentiated according to population of the administrative center of the community. Only for agricultural lands, the income from their use is taken into account according to the current methodology, however, they are taken into account through soil quality scores, which have not been updated since the 1980s.It was revealed that due to the fact that there is no indexation of the normative monetary valuation of agricultural land, the revenues of local budgets do not increase by at least UAH 0.6 billion every year on the scale of Ukraine.Key words: normative monetary valuation, land plots, territorial communities, local budgets, methodical recommendations.
Keywords: normative monetary valuation; land plots; territorial communities; local budgets; methodical recommendations.